2014
DOI: 10.1371/journal.pone.0090266
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Connexin Expression and Electrophysiological Properties in Stable Clones of the HL-1 Myocyte Cell Line

Abstract: The HL-1 atrial line contains cells blocked at various developmental stages. To obtain homogeneous sub-clones and correlate changes in gene expression with functional alterations, individual clones were obtained and characterised for parameters involved in conduction and excitation-contraction coupling. Northern blots for mRNAs coding for connexins 40, 43 and 45 and calcium handling proteins (sodium/calcium exchanger, L- and T-type calcium channels, ryanodine receptor 2 and sarco-endoplasmic reticulum calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 43 publications
5
44
1
Order By: Relevance
“…The electrical activity of cardiomyocytes creating a functional syncytium is synchronized and driven by the cells that have the fastest frequency of generation of spontaneous action potentials. Under this scenario, electrical coupling by gap junctions is the key determinant of conduction velocities in HL-1 cardiomyocytes [27]. In fact, when we recorded the spontaneous Ca 2+ oscillations in 4 cells of the same functional syncytium we found the same pattern of Fig.…”
Section: Localization and Functional Characterization Of D243gfs*4 Musupporting
confidence: 66%
“…The electrical activity of cardiomyocytes creating a functional syncytium is synchronized and driven by the cells that have the fastest frequency of generation of spontaneous action potentials. Under this scenario, electrical coupling by gap junctions is the key determinant of conduction velocities in HL-1 cardiomyocytes [27]. In fact, when we recorded the spontaneous Ca 2+ oscillations in 4 cells of the same functional syncytium we found the same pattern of Fig.…”
Section: Localization and Functional Characterization Of D243gfs*4 Musupporting
confidence: 66%
“…Our investigations showed that the as prepared electroactive substrate possess the ability to carry bioelectricity. It was found that the electroactive XSi‐PU3 is not only biocompatible in terms of cellular toxicity but (i) do not alter the intrinsic electrical characteristics of HL‐1 cells and (ii) is capable to conduct bioelectricity from two separated clusters (i.e., ca. 1 mm in Fig.…”
Section: Resultssupporting
confidence: 77%
“…B). While neonatal CMs show a fast increase in fluorescence in the neighbored cell, dye transfer was significantly slower in both SC‐CMs and HL‐1 cells, the latter being known for relatively low connectivity . Curves were fitted with a sigmoidal function according to the expected temporal kinetics of particle diffusion between two compartments (see below).…”
Section: Resultsmentioning
confidence: 99%